New insight in pediatric dentistry: preventive dentistry in allergy management protocol - Pradopo, Seno; Utomo, Haryono (Dental Journal (Majalah Kedokteran Gigi), 2007)
; "> The relationship between oral health and systemic diseases had been abundantly studied, however, mostly were related to adult such as cerebrovascular disease, cardiovascular disease, diabetes mellitus etc. Nevertheless, it was still uncommon that oral health also related to allergic disease. The field of pediatric dentistry is mostly related to preventive dentistry (i.e. prophylactic procedures, preventive orthodontic etc., but rarely related to preventive medicine such allergy prevention in children. Allergic diseases develop out of a close interaction between genetic predisposition and environmental triggers, and progress continuously since infancy regarding to the allergic march. Concerning to the partially developed immunity in children, children are more susceptible to infection and allergic diseases than adults. Unfortunately, infection and allergic diseases are interrelated; infection impaired allergy and vice versa. Poor oral health is closely related to infection; however, improving oral health is not included in allergy management protocol. In order to anticipate the future, dentist or especially pediatric dentist should be able to review about basic children immunity and oral mucosal immunity. Additionally, it is essential to explain to the parents and medical practitioners who are not familiar to this new paradigm. The objective of this study is to review articles related to children’s oral health and allergic symptoms. Regarding to the successful oral management of allergic symptoms, the propensity that improving oral health could be included in children’s allergy management protocol is likely.